Behavior of Peruvian carrot (Arracacia xanthorrhiza) and cassava (Manihot esculenta) starches subjected to heat-moisture treatment - Moraes, Jaqueline [UNESP]; Branzani, Rafaela S. [UNESP]; Franco, Celia M. L. [UNESP] (Wiley-Blackwell, 2014)
Peruvian carrot and cassava starches were isolated, adjusted to 30 and 35% moisture, and heated at 90 degrees C for 8 h. Structural and physicochemical characteristics of the treated starches were evaluated and compared. High performance anion exchange chromatography with pulsed amperometric detector (HPAEC-PAD), gel permeation chromatography (GPC), and amylose content, revealed that the HMT did not change the chemical structures of the starches. A large agglomeration of granules was observed from SEM, particularly in the Peruvian carrot starch. Crystalline patterns in Peruvian carrot and cassava starches changed from B to C and CA to A, respectively. Relative crystallinity decreased from 30 to 25% in Peruvian Carrot starch, and increased from 35 to 37% in cassava starch adjusted to 30% moisture. SF and peak viscosity decreased, breakdown was almost completely eliminated (particularly in the Peruvian carrot starch), and final viscosity increased. WAI and WSI increased as moisture levels of both starches increased. Gelatinization temperatures increased and enthalpy decreased. Degrees of gelatinization increased as the moisture level increased, reaching 33 and 72% in the cassava and Peruvian carrot starches, respectively. HMT strengthened the intra-and intermolecular interactions of starches and increased their stability during heating and shearing, but also caused a partial gelatinization in the starches, particularly in Peruvian carrot starch.
Keywords: Cassava; Gelatinization; Hydrothermal treatment; Peruvian carrot; Stability